2015
DOI: 10.15507/0236-2910.025.201504.063
|View full text |Cite
|
Sign up to set email alerts
|

Computational Efficiency for Optimization Problems of Revolution Shell S With Flutter Constra Ints

Abstract: ВЫЧИСЛИТЕЛЬНАЯ ЭФФЕКТИВНОСТЬ ДЛЯ РЕШЕНИЯ ЗАДАЧИ ОПТИМИЗАЦИИ ОБОЛОЧЕК ВРАЩЕНИЯ ПРИ ОГРАНИЧЕНИЯХ НА ФЛАТТЕРМ. В. Чугунов, Н. Д. Кузьмичёв, И. Н. Полунина ФГБОУ ВПО «Мордовский государственный университет им. Н. П. Огарёва» (г. Саранск, Россия) Теория и практика оптимизации занимает важное место в естествознании и технике. При этом алгоритмы решения оптимизационных задач требуют многократного обращения к процедуре вычисления функций оптимизации (прямой расчет). Эти функции, как правило, заданы алго-ритмически … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The windrow method of curing along with the storage by the hanging method can considerably reduce rotting since the temperature and humidity required by microbes were reduced by ventilation (Srinivasan & Shanmugam, 2006). Neck rots caused by B. aclada, B. allii, B. byssoidea causes dark brown outer scales and a water-soaked appearance (Chugunov & Li, 2015;Ji et al, 2018;Wang et al, 2014). Benzoyl and carbendazim at 0.5% showed better control of neck rots (Kumar et al, 2015).…”
Section: Harvest and Postharvest Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The windrow method of curing along with the storage by the hanging method can considerably reduce rotting since the temperature and humidity required by microbes were reduced by ventilation (Srinivasan & Shanmugam, 2006). Neck rots caused by B. aclada, B. allii, B. byssoidea causes dark brown outer scales and a water-soaked appearance (Chugunov & Li, 2015;Ji et al, 2018;Wang et al, 2014). Benzoyl and carbendazim at 0.5% showed better control of neck rots (Kumar et al, 2015).…”
Section: Harvest and Postharvest Practicesmentioning
confidence: 99%
“…Many of the researchers observed that this technique had an accuracy of more than 90% with a false positive rate lower than 10% (Haff & Toyofuku, 2008;Shahin et al, 2002;Speir and Haidekker, 2017;Tollner et al, 2005). A spectrometer in the wavelength region 670-870 nm could detect diseases in onions and the Monte Carlo simulation is an efficient tool for classifying healthy and diseased onions (Chugunov & Li, 2015). Field Asymmetric Mobility Spectrometry (FAIMS) was useful in the detection of soft rot with an accuracy of 69%-100% and sour skin at 58%-100% (Sinha et al, 2018).…”
Section: Type Of Lossmentioning
confidence: 99%